Pengembangan Pembelajaran Daring dan Media Online Terhadap Kemandirian Belajar yang Dimediasi Motivasi Belajar Siswa SMA - Namira Dwi Martina Yogi; Mardi Mardi; Aditya Pratama (LP. Ma'arif Janggan Magetan, 2023)
Technology has an important role, because it can improve the quality of education. The use of online media in the e-learning process is very important for transferring knowledge and can increase the effectiveness of online learning. Students who have high learning motivation are able to control their ability to learn independently. This study aims to examine the effectiveness of online learning and online media on learning independence mediated by learning motivation to explain this relationship. This research uses descriptive quantitative method. The sample used was 181 grade 11 high school students. The data in this study are primary data using a Likert scale. Sampling using proportional random. Data analysis technique used SmartPLS version 3.0 software. The results of the study stated that the Effectiveness of Online Learning had a positive and significant effect on Learning Independence, the Effectiveness of Online Learning had a positive and significant effect on Learning Motivation, Online Media had a positive and significant effect on Online Learning Effectiveness, Online Media had a positive and significant effect on Learning Independence, Online media has a positive and significant effect on learning motivation, learning motivation has a positive and significant effect on learning independence. The effectiveness of online learning has an effect on learning independence through learning motivation. Online media has a positive effect on learning independence through learning motivation. This research is an input for teachers to motivate students to learn independently and develop technological innovation and improve student learning abilities.